2013
DOI: 10.1371/journal.pone.0082122
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Accumulation in the Magnitude System

Abstract: Perceptual interferences in the estimation of quantities (time, space and numbers) have been interpreted as evidence for a common magnitude system. However, if duration estimation has appears sensitive to spatial and numerical interferences, space and number estimation tend to be resilient to temporal manipulations. These observations question the relative contribution of each quantity in the elaboration of a representation in a common mental metric. Here, we elaborated a task in which perceptual evidence accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 46 publications
12
77
0
Order By: Relevance
“…By contrast, probe distance was overestimated when probe duration was relatively shorter than the sample. In fact, this surprising result also confirms prior findings: Lambrechts et al (2013) found that the shorter the duration of a dynamic display, the larger the accumulated surface size was estimated to be. It was suggested that, in dynamic displays, when judgments of spatial or numerical magnitude depend on the integration of information over time, shorter stimulus durations lead to a higher concentration of spatial information per unit time, leading participants to overestimate spatial size (Lambrechts et al, 2013).…”
Section: Relevance To Magnitude Processingsupporting
confidence: 89%
See 3 more Smart Citations
“…By contrast, probe distance was overestimated when probe duration was relatively shorter than the sample. In fact, this surprising result also confirms prior findings: Lambrechts et al (2013) found that the shorter the duration of a dynamic display, the larger the accumulated surface size was estimated to be. It was suggested that, in dynamic displays, when judgments of spatial or numerical magnitude depend on the integration of information over time, shorter stimulus durations lead to a higher concentration of spatial information per unit time, leading participants to overestimate spatial size (Lambrechts et al, 2013).…”
Section: Relevance To Magnitude Processingsupporting
confidence: 89%
“…Furthermore, in a follow-up study, Droit-Volet (2010) showed that the perceptual distortions induced by click trains, which were thought to be specific to the temporal domain, also applied to spatial and numerical judgments but only if these stimuli were presented sequentially and their individual magnitudes accumulated. More recently, Lambrechts, Walsh, and Van Wassenhove (2013) found that, if spatial and numerical information was presented in a similarly dynamic (i.e., sequential) way to temporal information, then duration judgments were unaffected by the size or number of stimuli, contrary to many previous findings that size (Xuan, Zhang, He, & Chen, 2007) or number (Dormal, Seron, & Pesenti, 2006) distorts estimates of duration. These behavioral findings suggest that, when timing is compared with another magnitude dimension that is equally sequential or dynamic, then psychophysical differences in judgments of duration versus other magnitudes are no longer seen.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The account has received empirical support from behavioural demonstrations that different magnitude dimensions functionally interact with each other in perception (Meck, Church, & Gibbon, 1983;Lorenco & Longo, 2010;Martin et al, 2017;Lambrechts, Walsh, & van Wassenhove, 2013;Riemer, Diersch, Bublatzky, Wolbers, 2016) and recruit overlapping neural substrates (see Bueti & Walsh, 2009, for a review). On this account, a perceived duration is lengthened in the presence of a longer length (relative to a shorter one) because when both the duration and the length are mapped onto the common metric, the greater value of a longer length (relative to a shorter one) can pull on the duration value as a result of interference, resulting in a longer perceived duration.…”
mentioning
confidence: 99%